Socially sustainable housing and built environments to support the health and social inclusion of older adults: protocol for a scoping review and stakeholder consultation - Marie Elf; Jodi Sturge; Elke Miedema; Susanna Nordin (BMJ Open)
Introduction Housing and the ageing population are issues that pose challenges for social, health and economic policies. Therefore, there is a need for more knowledge on how to design housing and public infrastructure to improve the social engagement and well-being of older adults who age in place. This project aims to provide an overview of the existing literature on design features that support socially sustainable living environments for older adults.Methods and analysis A systematic scoping methodology was used to identify and summarise the findings. Four databases were searched (CINAHL (Cumulative Index to Nursing and Allied Health Literature), Scopus, Medline and Embase) to identify the articles. Articles were included if published in English in the last 15 years (eg, from January 2008 to June 2023) without restricting the study location or country. Articles were included if they were based on empirical qualitative, quantitative and mixed-method data. The results of the review will be discussed with a panel of 15 stakeholders (n=15) from Canada, Sweden and the Netherlands (five per country). The interdisciplinary stakeholders will have expertise in housing, architecture, engineering and social and health services. The consultations will provide content expertise to the literature findings and an opportunity to build evidence-based solutions that support the design of socially sustainable living environments for older persons.Ethics and dissemination Ethical clearance for this project has been granted by the Swedish Ethical Review Authority for Dalarna University (dnr 2023-01543-01) and the Natural Sciences and Engineering Sciences (NES) Ethics Committee at the University of Twente in the Netherlands (dnr 230407) has approved this project. Stakeholders will be asked to provide signed consent to participate in the study. The results of this project will be disseminated through web seminars, community advisory groups, peer-reviewed journals and policy documents to support the development of housing and public health policy.Trial registration number OSF, https://doi.org/10.17605/OSF.IO/PR2NC.